The activities of libraries under improving Russian legislation: a review of speeches at national scientific conferences 2011–2012 - S. P. Menschikova (Библиосфера, 2013)
The author provides an overview of presentations on the problem of the introduction of the Law № 83-FZ at national and international conferences during 2011–2012 (Moscow, St. Petersburg and Perm).